2013
DOI: 10.1017/s0022149x13000199
|View full text |Cite
|
Sign up to set email alerts
|

A molecular and ecological analysis of the trematodePlagiorchis elegansin the wood mouseApodemus sylvaticusfrom a periaquatic ecosystem in the UK

Abstract: The prevalence of the digenean Plagiorchis sp. was investigated in a natural wood mouse population (Apodemus sylvaticus) in a periaquatic environment. Classical identification was complemented with the use of molecular differentiation to determine prevalence and verify species identity. Use of the complete ITS1-5.8S rDNA-ITS2 and partial 28S rDNA gene sequences have confirmed that the species reported at this location was Plagiorchis elegans and not Plagiorchis muris as reported previously. This underlines the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…Sequencing of the ITS region proved to be useful for characterising Plagiorchis spp. (Tkach et al, 2000; Boyce et al, 2014), while the simultaneous examination of rDNA and mtDNA loci is suitable for molecular prospecting and further hypothesis testing on species delimitation (Nadler and Pérez-Ponce de León, 2011). Our findings revealed that Plagiorchis isolates from M. huberti , A. niloticus , and Crocidura sp., represented the same evolutionary lineage.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sequencing of the ITS region proved to be useful for characterising Plagiorchis spp. (Tkach et al, 2000; Boyce et al, 2014), while the simultaneous examination of rDNA and mtDNA loci is suitable for molecular prospecting and further hypothesis testing on species delimitation (Nadler and Pérez-Ponce de León, 2011). Our findings revealed that Plagiorchis isolates from M. huberti , A. niloticus , and Crocidura sp., represented the same evolutionary lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Due to time constraints, the gastrointestinal tract was analysed for a randomly-selected subset of the hosts. Isolated trematodes were characterised to the genus level based on their morphology using an Olympus CX41 microscope (following Boyce et al, 2014), counted to determine infection intensity (counts stopped at 61 individuals due to time constraints, therefore higher intensities are referred to as > 61 and the value 62 was used in statistical analyses), and preserved in 95% ethanol at −20 °C. Samples of liver from infected and uninfected M. huberti were preserved in 10% neutral-buffered formalin followed by routine processing for histopathological examination.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations